Early High-Titer Plasma Therapy to Prevent Severe Covid-19 in Older Adults - Libster, Romina; Pérez Marc, Gonzalo; Wappner, Diego; Coviello, Silvina; Bianchi, Alejandra; Braem, Virginia; Esteban, Ignacio; Caballero, Mauricio T; Wood, Cristian; Berrueta, Mabel; Rondan, Aníbal; Lescano, Gabriela; et al. (The New England journal of medicine, 2021)
High-titer convalescent plasma was compared with placebo in older adult patients within the first 3 days after the onset of symptoms of Covid-19 and documented SARS-CoV-2 infection. Disease progression was approximately half as common in patients who received convalescent plasma (16%) as in those who received placebo (31%).